IQ Motif-Containing GTPase-Activating Protein 2 (IQGAP2) Is a Novel Regulator of Colonic Inflammation in Mice - Ghaleb, Amr M. (PLoS One, 2015)
IQ motif-containing GTPase-activating protein 2 (IQGAP2) is a multidomain scaffolding protein that plays a role in cytoskeleton regulation by juxtaposing Rho GTPase and Ca(2+)/calmodulin signals. While IQGAP2 suppresses tumorigenesis in liver, its role in pathophysiology of the gastrointestinal tract remains unexplored. Here we report that IQGAP2 is required for the inflammatory response in colon. Mice lacking Iqgap2 gene (Iqgap2(-/-) mice) were resistant to chemically-induced colitis. Unlike wild-type controls, Iqgap2(-/-) mice treated with 3% dextran sulfate sodium (DSS) in water for 13 days displayed no injury to colonic epithelium. Mechanistically, resistance to colitis was associated with suppression of colonic NF-κB signaling and IL-6 synthesis, along with diminished neutrophil and macrophage production and recruitment in Iqgap2(-/-) mice. Finally, alterations in IQGAP2 expression were found in colons of patients with inflammatory bowel disease (IBD). Our findings indicate that IQGAP2 promotes inflammatory response at two distinct levels; locally, in colonic epithelium through TLR4/NF-κB signaling pathway, and systemically, via control of maturation and recruitment of myeloid immune cells. This work identifies a novel mechanism of colonic inflammation mediated by signal transducing scaffolding protein IQGAP2. IQGAP2 domain-specific blocking agents may represent a conceptually novel strategy for therapy of IBD and other inflammation-associated disorders, including cancer.